2002
DOI: 10.1073/pnas.072626099
|View full text |Cite
|
Sign up to set email alerts
|

The homeobox gene BREVIPEDICELLUS is a key regulator of inflorescence architecture in Arabidopsis

Abstract: Flowering plants display a remarkable range of inflorescence architecture, and pedicel characteristics are one of the key contributors to this diversity. However, very little is known about the genes or the pathways that regulate pedicel development. The brevipedicellus (bp) mutant of Arabidopsis thaliana displays a unique phenotype with defects in pedicel development causing downward-pointing flowers and a compact inflorescence architecture. Cloning and molecular analysis of two independent mutant alleles rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
284
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(293 citation statements)
references
References 51 publications
7
284
0
2
Order By: Relevance
“…bp-101 was isolated in our lab, originally from seeds of Ler ecotype that had been mutagenized by ethyl methanesulphonate (EMS). bp-101 has a shoot phenotype with defects in pedicel development as that have been previously reported by Douglas et al (2002) and Venglat et al (2002). Sequence analysis revealed that bp-101 carries a single base change in the homeodomain of the BP gene that alters Trp 326 into an opal stop codon.…”
Section: Plants and Growth Conditionssupporting
confidence: 67%
“…bp-101 was isolated in our lab, originally from seeds of Ler ecotype that had been mutagenized by ethyl methanesulphonate (EMS). bp-101 has a shoot phenotype with defects in pedicel development as that have been previously reported by Douglas et al (2002) and Venglat et al (2002). Sequence analysis revealed that bp-101 carries a single base change in the homeodomain of the BP gene that alters Trp 326 into an opal stop codon.…”
Section: Plants and Growth Conditionssupporting
confidence: 67%
“…Defective internode patterning is also observed in rice plants in which the related gene Oryza sativa homeobox15 (OSH15) is mutated (Sato et al, 1999). However, the flower stalks, or pedicels, are specifically shortened and curved downwards in bp mutants, owing to defects in cell division, cell elongation and cell differentiation (Douglas et al, 2002;Venglat et al, 2002), and it remains unclear which aspects of BP function are shared between this tissue and the SAM. KNAT6 and KNAT2 are part of a segmental chromosomal duplication in Arabidopsis, and single mutations in these genes do not affect shoot development (BellesBoix et al, 2006;Byrne et al, 2002).…”
Section: Class I Knox Genes In Meristem and Compound Leaf Developmentmentioning
confidence: 99%
“…3C,D) (Byrne et al, 2003;Douglas et al, 2002;Smith and Hake, 2003;Venglat et al, 2002). Plant architecture consists of repeating modules produced at the SAM called phytomers, each containing an internode, leaf and axillary meristem (Fig.…”
Section: Class I Knox Genes In Meristem and Compound Leaf Developmentmentioning
confidence: 99%
“…bp mutants are characterized by reduced stature, partial loss of apical dominance, and downward-oriented siliques (Douglas et al, 2002;Venglat et al, 2002;Smith and Hake, 2003). Figure 1 shows the phenotypes of the main inflorescences of the bp, knat2 bp, knat6 bp, and knat2 knat6 bp mutants.…”
Section: The Inactivation Of Knat6 Partially Rescues the Bp Phenotypementioning
confidence: 99%
“…BP plays a primary role in inflorescence growth, as indicated by bp mutants that exhibit reduced internode and pedicel lengths, bends at nodes, and downward-oriented siliques (Douglas et al, 2002;Venglat et al, 2002;Smith and Hake, 2003). PNY influences inflorescence architecture and fruit development (Byrne et al, 2003;Smith and Hake, 2003;Bhatt et al, 2004).…”
Section: Introductionmentioning
confidence: 99%